Antimicrobial effect of 2% tetracycline and 0,12% chlorhexidine on dental biofilm of healing abutments - Arízaga-Rujel, Gastón (2021)
Objective. To compare the antimicrobial effect of 2% tetracycline gel and 0,12% chlorhexidine gel on the dental biofilm of healing abutments on dental implants. Methods. This was an in vitro experimental cross-sectional study. Twenty-five biofilm samples were taken from the dental biofilm present on the area in contact with mucosa and the peri-implant groove of healing abutments of 19 patients. The samples were sowed in Petri dishes with Schaedler agar, three wells were made with a sterile punch and in each one tetracycline 2% in gel, 0,12% chlorhexidine in gel, and distilled water were placed in equal quantities. Then Petri dishes were incubated at 37 °C in an anaerobic medium for 48 hours after which inhibition halos were measured. Results. Both gels were inhibitors of dental biofilm growth. Tetracycline 2% in gel obtained larger diameters of inhibition halos than chlorhexidine 0,12% in gel, with a maximum of 51 mm and 17 mm respectively and a minimum of 21 mm and 10 mm, with means of 35 mm and 12.84 mm respectively. Conclusions. Tetracycline at 2% in gel had a higher antimicrobial effect than 0,12% in gel chlorhexidine on dental biofilm taken from healing abutments of dental implants.